Standard methods for the examination of water and wastewater - Lipps, William; Braun-Howland, Ellen Burton; Baxter, Terry E. (American Public Health Association, 2023)
Provides the most up-to-date, comprehensive resource for measuring the biological, chemical, and physical attributes of waters and offers guidance for choosing among available methods for specific elements and compounds.